Optimization of CTAB-based RNA extraction for in planta Fusarium oxysporum f. sp. cubense gene expression study - Poon, Nee Kiew; Rofina Yasmin Othman,; Katharina Mebus,; Teo, Chee How (Penerbit Universiti Kebangsaan Malaysia, 2019)
A crucial prerequisite for an insightful gene expression study is the quality of the nucleic acid extracted. High-quality nucleic acids allow comparative downstream analyses for both organisms during a phytopathogen infection. However, RNA extraction of pathogen-infected host materials usually involves extraction methods that are optimised individually for either the pathogen or the host. Different sets of buffers or specialised commercial kits are often required. In this study, a streamlined CTAB-based extraction protocol was optimised for both the pure culture of Fusarium oxysporum f. sp. cubense (Foc) and infected banana roots. Foc cultures were grown on PDA overlaid by a nylon membrane and total nucleic acids were successfully extracted from mycelia with a ratio of 100 mg mycelia powder mass to 2 mL of CTAB buffer. Using the optimised protocol, LiCl-precipitated RNAs showed higher values of A260/280 (2.064 ± 0.021) and A260/230 (1.937 ± 0.076) compared to ethanol precipitated RNAs. Similar observation was observed for inoculated banana roots where LiCl-precipitated RNAs showed higher values of A260/280 and A260/230 compared to ethanol precipitated RNAs. qRT-PCR analysis using a pair of Foc specific primers, FoTEF1α, confirmed that the LiCl-precipitated RNA was more suitable for downstream gene expression studies. This extraction protocol is applicable for Foc in planta gene expression study with a high potential to be extended to other filamentous fungal pathogens.